Budaya Belajar Mandiri dan Pendidikan Agama Islam di tingkat Sekolah Menengah Pertama - Nurhayati Nurhayati (Jurnal Ilmiah Iqra', 2011)
The present paper investigates whether autonomous learning can improve their Islamic knowledge. The favorable characteristics of autonomous learning are used as the basis for (1) arguing against the assumption that Indonesian learners are dependent on their teachers and (2) arguing for its adoptions in improving student. The paper also discusses how to incorporate autonomous learning in competency based curriculum.Key Words: Autonous learning, competency based curriculum